THE COGNITIVE PROCESS OF DIFFERENT GENDER IN WRITING ARGUMENTATIVE TEXT - Delima Melpiana Sianturi; Willem Saragih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
THE COGNITIVE PROCESS OF DIFFERENT GENDER IN WRITING ARGUMENTATIVE TEXT *Delima Melpiana Sianturi **Willem Saragih Abstract The purpose of this study was to describe the cognitive processes of students in writing argumentative text. The subjects were the students of SMA N 2 Percut Sei Tuan from two gender; they were five female students and five male students. It was descriptive qualitative research designs of which instrument are both writing and restropective interview. The research asked the subjects to write about argumentative text. A retrospective interview was conducted to the students after analyzing their argumentative writing in order to get the subject’s cognitive process taking place during the writing of their argumentative text. The results of the data analysis showed that the cognitive processes of the students of two gender were different. The cognitive process of male students in writing was in two stages: (a) organizing the idea, (b) translating the text. Besides, the cognitive process of female students in writing was in three stages: (a) organizing the ideas, (b) translating the text, and (c) reviewing the text. The cognitive process in writing argumentative rext occured with different process and different reason why they wrote the way it does.